TAO - A Software Platform for Autonomous Mobile Robots - Alves, Silas; Rosario, Joao M.; Ferasoli Filho, Humberto [UNESP]; Nunes, Ivan; IEEE (Ieee, 2012)
To date, different techniques of navigation for mobile robots have been developed. However, the experimentation of these techniques is not a trivial task because usually it is not possible to reuse the developed control software due to system incompabilities. This paper proposes a software platform that provides means for creating reusable software modules through the standardization of software interfaces, which represent the various robot modules.
Keywords: Software Platform; Mobile Robot; Robot System; Software Engineering